Teaching Authority Extention Of S1 Christian Religion Education Graduates As Class Teachers Through Thematic Curriculum Development - Lince Sihombing; Jumaria Sirait; Wanton Naibaho (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study aims at giving authority extensions of S1 Christian education graduates as class teachers through thematic curriculum development by doing and taking the answer for the following research problems: (1) How is the real condition of subject matters distribution of S1 Christian Education of IAKN Tarutung? (3) How is the subject matter distribution of S1 PGSD in general particularly S1 PGSD of HKBP/ Nomensen University Pematang Siantar? How is the result of the collaboration of S1 Christian Education and S1 PGSD based on Thematic Curriculum? This research was motivated by the scarcity of teaching opportunities of S1 Christian Education in entire Indonesia. In order to get the objectives of the research the used research design was Cresweel’s policy development research. The research result showed that the collaboration of S1 Christian Education and S1 PGSD based on the Thematic curriculum theoretically gave effective result in extending the teaching authority of S1 Christian Education as Class teachers of Primary Students of Primary School in entire Indonesia.